A protocol to assess the wear of head/neck taper junctions in large head metal-on-metal (LHMoM) hips - Underwood,RJ; Kocagoz,SB; Smith,R; Sayles,RS; Siskey,R; Kurtz,SM; Cann,PM (ASTM Special Technical Publication, 2013)
Researchers have hypothesized that the increased revision rate of LHMoM (Large Head Metal-on-Metal) hips compared to MoM hip resurfacings may be attributed to corrosion and wear at the head neck taper junction. Studies have reported visual evidence of fretting and corrosion at the taper junction, but no method has been described in the literature to quantify the amount of material lost from the taper junction. This paper describes a measurement protocol using a Taylor Hobson Talyrond Roundness instrument that allows the simultaneous measurement of surface form (wear) and surface topography (roughness). The methodology allows the measurement of the taper angle, geometry of worn region (depth, length), 3D surface maps and surface topography of the head conical taper. The accurate quantification of the taper geometry, wear and topography is essential to the understanding of the in vivo wear and corrosion mechanisms of taper junctions in LHMoM hips. Copyright © 2013 by ASTM International.